The Relationship between Reactive Oxygen Species and Cardiac Fibrosis in the Dahl Salt-Sensitive Rat under ACEI Administration - Ryou Tanaka; Miki Shimizu (Veterinary Medicine International)
Enalapril maleate, the oldest and most widely distributed ACEI, and alacepril, the newest and antioxidant ACEI, were compared in the point of cardioprotective effect for Dahl salt-sensitive rat. In order to evaluate the correlation between the three factors, cardiac fibrosis and blood pressure/oxidative-stress marker (tissue TBARS), index of correlation was calculated. The results showed a significant difference in cardiac fibrosis between high-dose alacepril (30 mg/kg/day, group H) and enalapril maleate (10 mg/kg/day, group E). There was significant correlation between cardiac fibrosis and oxidative-stress marker, although there was no correlation between cardiac fibrosis and blood pressure. Fibrosis was more influenced by oxidative stress not by blood pressure, we should not select ACEI only by blood pressure-lowering effect and should more consider cardioprotective effects of ACEI.